2009
DOI: 10.1002/elps.200900198
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic sample injection for high‐sensitivity CZE (part 2): Improving the quantitative repeatability and application of electrokinetic supercharging‐CZE to the detection of atmospheric electrolytes

Abstract: Electrokinetic supercharging (EKS) is defined as a technique that combines electrokinetic sample injection with transient ITP. Quantitative repeatability of EKS-CZE and the other CE methods using electrokinetic sample injection process is usually inferior in comparison with the CE methods using hydrodynamic or hydrostatic injection. This is due to some effects, such as the temperature change and the convection of the sample solution in the reservoir, as well as the change of the distance between an electrode a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…In its basic design, EKS lowered the LOD of Er down to 0.27 mg/L (1.6 nM) [11]. The following studies demonstrated that the electrode configuration and position significantly affect the efficiency and reproducibility of sample injection [16,17]. Importantly, by increasing the distance between tips of the electrode and the capillary in vertical direction (abbreviated as D e/c hereafter), which are located in a typical sample vial, the LOD of erbium was improved to an impressive threshold of 0.02 mg/L (0.12 nM) [16].…”
Section: Introductionmentioning
confidence: 97%
“…In its basic design, EKS lowered the LOD of Er down to 0.27 mg/L (1.6 nM) [11]. The following studies demonstrated that the electrode configuration and position significantly affect the efficiency and reproducibility of sample injection [16,17]. Importantly, by increasing the distance between tips of the electrode and the capillary in vertical direction (abbreviated as D e/c hereafter), which are located in a typical sample vial, the LOD of erbium was improved to an impressive threshold of 0.02 mg/L (0.12 nM) [16].…”
Section: Introductionmentioning
confidence: 97%
“…Using a long Dec (8 mm), the peak heights for PTPB and DPB were, respectively, 2.2 and 1.2 times higher than those obtained using the default Dec (0.5 mm). The peak heights for MPB and phenol were, respectively, 0.41 and 0.40 times lower than those obtained using the default Dec. Hirokawa et al 38 determined atmospheric electrolytes using EKS-CZE with a default Dec (1.1 mm) and a long Dec (19.5 mm). The LODs obtained using the long Dec were improved ca.…”
Section: Effect Of the Electrode Configurationsmentioning
confidence: 95%
“…The analytical conditions, time of water plug injection, time, and voltage of sample introduction were examined and optimized. Boer and Ensing, 36 and Hirokawa et al 37,38 reported that the efficiency of EKI and EKS is strongly related to the electrode configurations. Therefore, we investigated the effects of the distance between the tip of the electrode and a capillary end (Dec) on the peak heights for the analytes listed above using FASI.…”
Section: Introductionmentioning
confidence: 99%
“…Following this work, the authors provided a new strategy for viable improvement in the quantitative repeatability of EKS [52]. They proposed that variation in the distance between the electrode and the capillary end will adversely affect the quantitative repeatability of any EKI procedure.…”
Section: Eks In Capillary Electrophoresismentioning
confidence: 98%